Factors influencing customer satisfaction on food service establishment in Malaysia and other Asean countries / Nor Adilah Mohd Nazlin & Nor Hazimah Ishak - Mohd Nazlin, Nor Adilah; Ishak, Nor Hazimah (Faculty of Hotel and Tourism, 2018)
The customer satisfaction is the expectations of the customer are met with the experience by them. Factors influencing customer satisfaction is important in determine the success of the food service establishment that concurrently effect food service industry. However, the food service establishment are too wide and need a long time to discuss. Hence, in this thesis it has chosen few selected establishment (i.e. Restaurant, Cafeteria and Fast food) and few selected Asean countries (i.e India, China, Korea and Japan) to discuss the factors influencing customer satisfaction that hope may help to contribute some knowledge in boosting the profit of foodservice industry in future. Furthermore, in this topic, it also discusses the similarities and dissimilarities of the most factors influencing customer’s satisfaction on the food service establishment in Asean countries. So that, country in Asean can improve and generate their food service organization in the higher level in the world. The databases were mainly accessed from different online resources such as Science Direct, Emerald insight, Google scholar, academia.edu, e-books, and also from authorities website (i.e Ministry of Health and World Health Organization etc) to get the accurate data. All the linked accordingly to create complete comprehension review on factors influencing customer satisfaction among Asean countries. Only few of the articles can be discussed due to limitation of time. Although it is not many in order to cover the generalization of the countries and factors, it is hope can be part of the new contribution to the knowledge in factors influences customer satisfaction that that may show some good example to be implemented later in Malaysia and vice versa.